Taking Blender to the next level : implement advanced workflows such as geometry nodes, simulations, and motion tracking for Blender production pipelines /: implement advanced workflows such as geometry nodes, simulations, and motion tracking for Blender production pipelines. (2022) - Lotter, Ruan
No abstract available